Slow and Fast Responses: Two Mechanisms of Trial Outcome Processing Revealed by EEG Oscillations - Novikov, Nikita A.; Nurislamova, Yulia M.; Zhozhikashvili, Natalia A.; Kalenkovich, Evgenii E.; Lapina, Anna A.; Chernyshev, Boris V. (Frontiers in Human Neuroscience, 2017)
Cognitive control includes maintenance of task-specific processes related to attention, and non-specific regulation of motor threshold. Depending upon the nature of the behavioral tasks, these mechanisms may predispose to different kinds of errors, with either increased or decreased response time of erroneous responses relative to correct responses. Specifically, slow responses are related to attentional lapses and decision uncertainty, these conditions tending to delay response times of both erroneous and correct responses. Here we studied if response time may be a valid approximation distinguishing trials with high and low levels of sustained attention and decision uncertainty. We analyzed response-related and feedback-related modulations in theta, alpha and beta band activity in the auditory version of the two-choice condensation task, which is highly demanding for sustained attention while involves no inhibition of prepotent responses. Depending upon response speed and accuracy, trials were divided into slow correct, slow erroneous, fast correct, and fast erroneous. We found that error-related frontal midline theta was present only on fast erroneous trials. The feedback-related frontal midline theta was equally strong on slow erroneous and fast erroneous trials. Late post-response posterior alpha suppression was stronger on erroneous slow trials. Feedback-related frontal beta was present only on slow correct trials. The data obtained cumulatively suggests that response time allows distinguishing the two types of trials, with fast trials related to higher levels of attention and low uncertainty, and slow trials related to lower levels of attention and higher uncertainty.